Pediatric Endourology Techniques - Godbole, Prasad P. (Springer London : Imprint: Springer, 2007)
Pediatric Endourology Techniques comprehensively covers the practical aspects of the various endourological procedures in children. The surgeon can read and watch the procedure which includes some helpful tips and tricks to make the procedure easier and safer. Essential reading and viewing for pediatric urologists, pediatric surgeons, and residents in both areas, it will also benefit greatly the adult surgeons who occasionally deal with children.